2020
DOI: 10.4018/jeco.2020100104
|View full text |Cite
|
Sign up to set email alerts
|

How to Make Effective Product Review Videos

Abstract: Extant research on online user-generated content, especially product reviews, has consistently examined the effects of textual reviews on consumers and has ignored an emerging and popular review format such as product review video (PRV) on YouTube. Specifically, no research exists that suggests how to develop an effective PRV. The present article addresses this gap by examining the effects of three important attributes of PRVs – review depth, review frame, and review disposition, on consumers' attitude toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, there are still few studies conducted about what important features of vWOM that make them useful and can aid in creating positive customer perceptions (Ghosh, 2020). Numerous studies have found that vWOMs are posted on social commerce platforms to share experience or information with online customers that need it (Bezbaruah & Trivedi, 2020;Jain et al, 2018;Sokolova & Kefi, 2020;Tellis et al, 2019;Yang et al, 2017;Zhu et al, 2020) , but to date, there is a lack of studies looking at trusted attributes of vWOM, and how communication is carried out through the videos that can be trusted and influence purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still few studies conducted about what important features of vWOM that make them useful and can aid in creating positive customer perceptions (Ghosh, 2020). Numerous studies have found that vWOMs are posted on social commerce platforms to share experience or information with online customers that need it (Bezbaruah & Trivedi, 2020;Jain et al, 2018;Sokolova & Kefi, 2020;Tellis et al, 2019;Yang et al, 2017;Zhu et al, 2020) , but to date, there is a lack of studies looking at trusted attributes of vWOM, and how communication is carried out through the videos that can be trusted and influence purchase intention.…”
Section: Introductionmentioning
confidence: 99%